Network analysis on depressive symptoms and big five personality traits of community elderly over 60 years old: a cross-sectional study - Mo Zhu; Yanqun Zheng; Yuan Fang; Qi Qiu; Xia Li (Frontiers in Psychiatry)
BackgroundThe global population is undergoing significant aging, with the elderly facing prominent physical and mental health challenges. Geriatric depression is becoming increasingly prevalent, imposing a heavy burden on healthcare and caregiving. This study employs network analysis to explore the relationship between geriatric depressive symptoms and the Big Five personality traits, aiming to provide a theoretical basis for preventing and intervening in geriatric depression.MethodsA total of 585 residents aged 60 and above, with an average age of 67.14 ± 5.26 years, were included in this study. The Geriatric Depression Scale-15 was used to assess depressive symptoms, and the 60-item version of the Big Five Personality Inventory was used to assess personality traits. The network model was constructed in R using the qgraph, bootnet, and networktools packages, applying LASSO regularization with EBIC for model selection. Network centrality was evaluated using Strength and Bridge Strength as indicators. Meanwhile, network comparison analyses were conducted for different genders.ResultsThe model included 45 edges, 29 of which had non-zero estimates, with an average edge weight of 0.038. Openness had negative connections with withdrawal apathy-vigor (WAV) and hopelessness; Conscientiousness had a negative connection with dysphoric mood; Extraversion had a negative connection with WAV; Agreeableness had a negative connection with anxiety; and Neuroticism had positive connections with dysphoric mood, WAV, anxiety, memory complaints, and hopelessness. According to the strength centrality ranking, the top four nodes were Neuroticism, Conscientiousness, dysphoric mood, and hopelessness. The nodes with higher bridge strength were Neuroticism, dysphoric mood, and WAV. The analysis stratified by gender revealed that Neuroticism consistently exhibited the highest strength and bridge strength. In terms of the strength of depressive symptoms, dysphoric mood was most prominent in males, while hopelessness was most significant in females. Regarding bridge strength, anxiety symptoms had the highest bridge strength in males, whereas dysphoric mood had the highest bridge strength in females.ConclusionDifferent personality traits show varied associations with geriatric depressive symptoms. Neuroticism is crucial in the Personality–Depressive Symptoms network, and gender differences exist in this relationship. These findings may offer guidance for the prevention and treatment of depressive symptoms in older adults.